2019
DOI: 10.1177/1745691618812684
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contributions to Loneliness and Their Relevance to the Evolutionary Theory of Loneliness

Abstract: Loneliness is a negative and distressing emotional state that arises from a discrepancy between one’s desired and achieved levels of social connectedness. The evolutionary theory of loneliness (ETL) posits that experiencing loneliness is an inherited adaptation that signals that salutary social relations are endangered or damaged and prompts people to reconnect to significant others. The basic tenets of the ETL has led researchers to examine the genetic underpinnings of loneliness. The current review provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 115 publications
7
48
0
Order By: Relevance
“…According to the results of the present meta-analysis, the mean levels of loneliness appear to decrease in childhood but to be rather stable afterward. This finding is especially important, as it has been recently demonstrated that loneliness and neuroticism share a common genetic basis (Abdellaoui et al, 2019; Aitken Schermer & Martin, 2019; for a review, see Spithoven, Cacioppo, Goossens, & Cacioppo, 2019). These findings might indicate that neuroticism reflects the overall propensity of individuals to experience negative affect, whereas loneliness reflects the tendency to experience negative affect particularly in social situations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…According to the results of the present meta-analysis, the mean levels of loneliness appear to decrease in childhood but to be rather stable afterward. This finding is especially important, as it has been recently demonstrated that loneliness and neuroticism share a common genetic basis (Abdellaoui et al, 2019; Aitken Schermer & Martin, 2019; for a review, see Spithoven, Cacioppo, Goossens, & Cacioppo, 2019). These findings might indicate that neuroticism reflects the overall propensity of individuals to experience negative affect, whereas loneliness reflects the tendency to experience negative affect particularly in social situations.…”
Section: Discussionmentioning
confidence: 97%
“…These differences are also mirrored in moderate meta-analytic phenotypic correlations between loneliness and neuroticism in the magnitude of r=.30 (Buecker et al, 2018). Thus, despite their common core, several mechanisms seem to pull the development of loneliness and neuroticism in different directions in the long run (Spithoven et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another study using data from four nationally representative samples has shown that between 50 and 60% of inter-individual differences in loneliness can be attributed to stable, trait-like sources . Finally, from a behavior genetic point of view, approximately 40% of the phenotypic variation in loneliness has been found to be accounted for by genotypic variation (for reviews, see Goossens et al 2015;Spithoven et al 2019). Taken together, this line of research suggests that inter-individual differences in loneliness are largely stable over time.…”
Section: Loneliness As a Predictor Of Relationship Satisfactionmentioning
confidence: 99%
“…The role of specific classes of long noncoding RNAs in resiliency or susceptibility to develop depression with a reciprocal response to antidepressant treatment is underlined [83]. Epigenetic changes in the signalling pathway of glucocorticosteroids (e.g., NR3C1, FKBP5), with regard to serotonergic neurotransmission (e.g., SLC6A4) and in the area of genes encoding neurotrophic factors (e.g., BDNF), seem to be the most promising therapeutic targets for future research [23,84].…”
Section: Further Directions Ofmentioning
confidence: 99%